Repelência e deterrência alimentar de vaquinhas por óleos de nim e cinamomo aplicados em folhas de feijoeiro - Sardinha de Souza, Bruno Henrique [UNESP]; Costa, Eduardo Neves [UNESP]; Ribeiro, Zulene Antonio [UNESP]; Forim, Moacir Rossi; Boica Junior, Arlindo Leal [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2014)
This work aimed to evaluate the repellent and deterrent effect of the application of concentrations of neem and chinaberry oil on bean leaves on the leaf beetles Diabrotica speciosa (Germar) and Cerotoma arcuata (Olivier). The concentrations of neem oil tested were 0.625, 1.25, 2.50, 5.00, 10.00 and 20,00 mL, corresponding respectively to 1, 2, 4, 8, 17 and 33 ppm of azadirachtin A and the concentrations of chinaberry oil used were the same used to neem oil, corresponding, however, to 1.875, 3.75, 7.50, 15.00, 30.00 and 60.00 mg mL(-1) of chinaberry extract, respectively. For the free-choice tests, glass containers were used as arenas, whereas for the no-choice tests Petri dishes were used, where in both one insect per treatment was released in the center. Attractiveness was evaluated in predetermined time periods, in addition to the leaf consumption, at the end of the experiment. Neem oil is repellent to D. speciosa and C. arcuata, with more efficient results at the 5.00, 10.00 and 20.00 mL concentrations. All concentrations of neem oil reduce leaf consumption of both insects, except in the no-choice test with D. speciosa, in which only the 10.00 and 20.00 mL concentrations are deterrent. Chinaberry oil provides high repellent activity on both leaf beetle species, and the 10.00 and 20.00 mL concentrations stood out. The 10.00 and 20.00 mL concentrations of chinaberry oil are deterrent to D. speciosa and C. arcuata.
Feeding reppelency and deterrence of leaf beetles by neem and chinaberry oils applied on bean leaves
Keywords: Diabrotica speciosa; Cerotoma arcuata; Phaseolus vulgaris; Azadirachta indica; Melia azedarach